Assaying mitochondrial cell number, morphology and respiration status in the emerging three lineages of the preimplantation stage mouse embryo . - Kutsyna, Valeriy (Jihočeská univerzita, 2023)
The aim of this master thesis was to assay mitochondrial cell number, morphology and respiration status in the emerging three lineages of the preimplantation stage mouse embryo.
Assaying mitochondrial cell number, morphology and respiration status in the emerging three lineages of the preimplantation stage mouse embryo .
Keywords: preimplantation mouse embryonic development; blastocyst; trophectoderm; primitive endoderm; epiblast; mitochondria; p38-MAPK inhibition (p38-MAPKi); preimplantation mouse embryonic development; blastocyst; trophectoderm; primitive endoderm; epiblast; mitochondria; p38-MAPK inhibition (p38-MAPKi)